Access to financial services: towards an understanding of the role and impact of financial exclusion in Sub-Saharan Africa - Ndlovu, Godfrey (Department of Finance and Tax, 2018)
This thesis investigates the nature and extent of financial inclusion in Sub-Saharan Africa (SSA). It sequentially investigates this in three related studies. The first study examines the impact of access to finance on poverty, while the second investigates the extent to which cross-country structural and macroeconomic variations contribute to the observed variations in the levels of financial inclusion. Finally, because both financial inclusion and financial stability have been embraced as key policy initiatives over the past decade, the third study examines the nature of relationship between these two policy goals. The first paper uses household-level data from FinScope Surveys conducted in eight SSA countries between 2014 and 2015 to examine the impact of access to finance on household wealth. The few studies which have looked at this relationship in the past apply a linear estimation and thus inadvertently assume a uniform distribution across all levels of poverty. This study examines the heterogeneous impact of access to finance along the entire wealth distribution line using a Re-centered Influence Function (RIF) regression model. Further, to eliminate potential endogeneity, an instrumental variable quantile approach is implemented. Results from both estimations indicate that the unconditional effect of access to finance on poverty is non-monotonic. For most of the countries, the effect is highest at the median level, and very low at the bottom of the wealth index. This suggests that the extension of formal financial services disproportionately benefits the middle-class more than the very-poor and rich categories. The second paper uses macroeconomic data obtained from various World Bank databases over the period 2004-2014 to examine the extent to which the observed cross-country variations in financial inclusion are mirrored by country-specific structural and macroeconomic characteristics. To conceptualize, the study uses a benchmark model to establish the optimal level of financial inclusion given the country's fundamentals, and thus provide a meaningful cross-country comparison. The key structural and policy factors that determine the extent of the gap between the actual and predicted levels of access to finance are analysed via a fixed-effects model based on selected SSA countries. The results suggest the existence of a gap in access to finance within the region, compared to their potential. The gap is wider in banking systems with high concentration, low proportion of foreign banks and poor economic conditions. The final paper empirically examines the theoretical ambiguity between financial inclusion and stability. Theory provides conflicting views on whether the two are complimentary, or mutually exclusive. This paper examines this dynamic relationship via a system-GMM panel estimation model using a panel of 40 countries from the SSA region over the period 2004-2014, while controlling for both bank-specific and macroeconomic-wide factors. The results indicate that financial inclusion has a positive impact on bank stability, however, high market power within the banking systems and poor institutional framework tends to undermine the impact of financial inclusion on stability. Overall, the results provide evidence that the existing portfolio of formal financial services does not provide sustainable solutions to poverty eradication in terms of meeting the unique needs of the poorer members of the societies. This ultimately widens the gap between the poorest and the middle-class which further complicates the poverty structure. Therefore, there is a need for more investment on improving both the range of existing product offering and the financial capabilities of the poor, in order to improve their participation in financial markets. Demand-side policies should focus on increasing the bankable population by improving both awareness and usage of financial services and products. Supply-side policies should seek to eliminate market frictions by reducing concentration levels, improve competiveness through relaxation of entry restrictions, and opening the market to foreign institutes and non-banking players, and thus improve innovation in both new products offering and service delivery. This work further argues that financial inclusion is not only a developmental or welfare issue, but has positive ramifications on the banking system. Therefore, to be effective financial inclusion policies should adopt a market systems approach to development, which recognizes the importance of support structures and seek to benefit the poor by incentivizing service providers to improve product quality, variety and returns, and thus create value throughout the value chain. An effective approach should also embrace the role of macro-prudential regulatory and supervisory framework, as an indispensable tool, not only in governing the behavior of financial services providers, but because of its efficacy in building consumer confidence- a key element for increased access and usage of financial services.